2008
DOI: 10.1186/1757-1626-1-335
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral atypical calcification in nongalenic pial arteriovenous fistula: a case report

Abstract: Nongalenic intradural arteriovenous fistulas, although uncommon, are clinically important. Choosing the appropriate therapeutic approach has been a controversial issue within the last decade.A 15-year-old male was presented with a calcified nongalenic arteriovenous fistula in the left parietal region, supplied by the left middle cerebral artery, and draining into the left lateral sinus. The patient was managed surgically with traditional clipping the feeder artery, along with piecemeal resection of the huge ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…9,12 In this case, the dystrophic calcification shown in the images can be an accumulation of waste product in the paravascular space that cannot be washed out because of the inverse hydrostatic pressure 29 and not only the result of chronic hypoxic insult described by others. 9,15,27,29,35,42 This evolving understanding of CSF dynamics will help us bring better care and make better decisions, but many animal models and clinical analyses on hydrocephalus will be needed to fully understand the hydrodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…9,12 In this case, the dystrophic calcification shown in the images can be an accumulation of waste product in the paravascular space that cannot be washed out because of the inverse hydrostatic pressure 29 and not only the result of chronic hypoxic insult described by others. 9,15,27,29,35,42 This evolving understanding of CSF dynamics will help us bring better care and make better decisions, but many animal models and clinical analyses on hydrocephalus will be needed to fully understand the hydrodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…They also reinforced the concept that because the pathologic features of pial NGAVFs arise mainly from their high flow nature, elimination of the shunt by fistula closure is the treatment of choice and resection of the lesion is not necessary [1]. While this is generally accepted, there have been reports of cases since that were thought to require surgical resection due to atypical anatomy such as a large calcified mass and many small feeders not found on angiography [39,46].…”
Section: Treatmentmentioning
confidence: 91%
“…Angiographic features considered unfavorable for endovascular treatment include a normal cortical vein anastomosing with the NGAVF venous outflow channel very near the fistula site or the presence of one or more arterial feeders that is technically difficult to access [1]. The role of surgery has waned in the last 15 years with improvements in endovascular techniques but remains an important treatment modality [2,16,19,21,[38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Treatmentmentioning
confidence: 99%
“…The mechanism of calcification of the pial AVFs involved a dystrophic process due to hypoperfusion caused by the steal phenomenon or venous congestion over a long time period. 62…”
Section: Treatmentsmentioning
confidence: 99%
“…In 2008, Tabatabai et al reported one case with giant parietal NGPAVF, which was successfully removed, although the surgery was very difficult. 62 In addition, in 2015, da Silva et al reported one case of NGPAVF in which variceal dilatation caused a significant mass effect due to its very stiff and thick walls. The variceal dilatation was resected due to this mass effect.…”
Section: Mass Effectmentioning
confidence: 99%